GTA Weldability of Rolled High-Entropy Alloys Using Various Filler Metals - Hyunbin Nam; Seonghoon Yoo; Junghoon Lee; Youngsang Na; Nokeun Park; Namhyun Kang (Metals, 2020)
Gas tungsten arc (GTA) weldability of rolled CoCrFeMnNi high-entropy alloys (HEAs) was conducted using stainless steel (STS) 308L and HEA fillers. Microstructure and mechanical properties of the welds were examined to determine GTA weldability of the rolled HEA. The welds had no macro-defects, and component behaviour between base metal (BM) and weld metal (WM) showed significant differences in the weld using the STS 308L filler. Macro-segregation of Fe components was confirmed in the central region in the WM using the STS 308L filler. Because the columnar grain sizes of all the WMs were larger than those of the rolled HEA BM irrespective of the filler metals, the tensile properties of the GTA welds were lower than those of the rolled HEA BM, and the tensile fracture occurred in the centreline of each weld. In particular, the tensile properties of the weld using the STS 308L filler deteriorated more than those of the HEA weld. This was induced by the formation of macro-segregation and severe martensite transformation in the centreline of WM. To enhance the weldability of the rolled HEA, the formation of macro-segregation and coarse grains in the WM of GTA welds must be prevented.